Factors influencing behavioral intention to use m-learning and the mediation role of user satisfaction - Ng, Kim-Soon; Ibrahim, Mohamud Ahmed; Ahmad, Abd Rahman; Ng, Mei Xin Sirisa (American Scientific Publishers, 2018)
The rapid development of mobile technologies has resulted in a phenomenal growth in the number of youth using the mobile devices for their learning in Malaysia. An understanding on the influence of mobile technologies and its intention to use for learning are crucial. However, there is still a lacking of attention being given by researchers related to this area. Thus, the aim of this study is to investigate the factors influencing intention to use m-learning among students at Malaysian technical universities. The research model has been adopted by combining two related theoretical models, the unified theory of acceptance and use of technology (UTAUT), and the IS success model. A total of 400 sets of data were collected from four Malaysia technical universities using purposeful structured random sampling and self-administrated survey questionnaire. The SPSS AMOS software has been used to test the model of its goodness of fit and the relationships between the variables. The results revealed that the performance expectancy, perceived playfulness, and self-management of learning have a positive significant influence to predict behavioral intention to use m-learning, while social influence and effort expectancy show a negative impact on the behavioral intention. The performance expectancy, self-management of learning and effort expectancy are positively significantly related to user satisfaction while the social influence, and perceived playfulness are negatively significantly related to user satisfaction. It was also found that user satisfaction partially mediates the relationship between performance expectancy and behavioral intention to use m-learning, and the relationship between factors influencing learning and behavioral intention to use m-learning. However, user satisfaction fully mediates the relationship between effort expectancy and behavioral intention to use m-learning.